2014
DOI: 10.1039/c4ob01304b
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of putative montamine and a proposed structural reassignment

Abstract: The natural product montamine was originally assigned as a homodimer of moschamine linked by a N-N' bond at the serotonin side-chain. A total synthesis of the reported structure has shown this to be incorrect. Analysis of the spectroscopic data suggests that the dimerization site has been incorrectly assigned, and montamine is likely to be a 4,4'-bismoschamine natural product previously described in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A total synthesis of the reported structure by Sperry and co-workers showed this assignment to be incorrect. They proposed that montamine ( 5 ) was likely to be 4,4″-bis­( N -feruloyl)­serotonin ( 4 ) upon analysis of the spectroscopic data . Unfortunately, they could not confirm this proposed structural reassignment of montamine ( 5 ) because the NMR data for these two natural products were reported in different solvents (CD 3 OD and DMSO- d 6 , respectively) and authentic samples of both the natural products necessary for a full spectroscopic comparison in the same NMR solvent were not available.…”
mentioning
confidence: 99%
“…A total synthesis of the reported structure by Sperry and co-workers showed this assignment to be incorrect. They proposed that montamine ( 5 ) was likely to be 4,4″-bis­( N -feruloyl)­serotonin ( 4 ) upon analysis of the spectroscopic data . Unfortunately, they could not confirm this proposed structural reassignment of montamine ( 5 ) because the NMR data for these two natural products were reported in different solvents (CD 3 OD and DMSO- d 6 , respectively) and authentic samples of both the natural products necessary for a full spectroscopic comparison in the same NMR solvent were not available.…”
mentioning
confidence: 99%
“…[46] Montamine was isolated from seeds of the ornamental plant Centaurea montana and showed significant anti-colon cancer activity in vitro (IC 50 =43.9 μmol/L). [49] They proposed that montamine was likely to be 4,4"-bis(N-feruloyl)serotonin upon analysis of the spectroscopic data. A total synthesis of the reported structure by Sperry and co-workers showed this assignment to be incorrect.…”
Section: Total Synthesis Of 44″-bis(n-feruloyl)serotoninmentioning
confidence: 99%
“…3 The 1 H NMR signals for the αand β-methylene protons in montamine (2) were significantly upfield relative to those reported for moschamine (1), a shielding effect suggested to ensue from restricted rotation about the N-N′ bond placing the methylenes in close proximity to the aromatic rings. In recent reports, 4,5 we described the synthesis of the diacylhydrazide structure 2 assigned to montamine 6 and found that the 1 H and 13 C NMR data differed dramatically from that of natural product. Most notably, the 1 H NMR signals corresponding to the αand β-methylene protons in synthetic diacylhydrazide 2 were not distinctively upfield (Fig.…”
Section: Introductionmentioning
confidence: 99%